Deformation Measurements and Analysis with Robust Methods: A Case Study, Deriner Dam - Konakoğlu, Berkant; Gökalp, Ertan (Fırat University, 2018)
Dams, one of the country's most natural and cheapest way to product energy, are built for energy production, agricultural activities and flood protection. Dams with high construction costs are subject to deformation due to some physical factors. Therefore, dams should be kept safe to prevent possible dam accidents, loss of life and property. Engineering structures (such as dams) should be monitored periodically by geodetic and non-geodetic techniques. Deriner dam is Turkey's highest double-curved concrete arch dam. In this study, we monitored deformation with GPS measurements. For this purpose, two period static GPS measurements were performed on the reference and object points in the study. Afterwards, GPS measurements were adjusted separately with respect to free adjustment method and then deformation analysis were carried out by using the adjusted coordinates and their cofactor vectors. Iterative Weighted Similarity Transformation (IWST) and Least Absolute Sum (LAS) methods were used as deformation methods to detect the displacement of the reference and object points.
Keywords: Engineering; Mühendislik